Optimalisasi G-Drive dalam Pengarsipan Digital Pelatihan pada Guru SD di Kecamatan Medan Belawan - Tanjung, Ahmad Albar; Muliyani (Jurnal Pengabdian Masyarakat Inovasi, 2024)
School administrative management at SDN 066670 Sicanang, Medan Belawan District, still faces obstacles in terms of document archiving efficiency, which is dominated by physical media. The risk of data loss and the difficulty of document accessibility are the main urgencies for digitalization. This community service activity aims to optimize the use of Google Drive as a digital archiving medium for teachers and educational staff. The method used is a descriptive workshop which includes the preparation, implementation (lectures, simulations, and intensive mentoring), and monitoring stages. The results of the activity show a significant increase in the participants' digital competence. Before the training, only 20% of participants had a high level of knowledge, but after the training, this figure increased sharply to 80%. Teachers are now able to manage folder architecture systematically and utilize real-time collaboration features. In conclusion, Google Drive is a flexible, functional, and optimal archiving solution to support modern school administration. The recommendation of this activity is the need for school policies to standardize digital archiving to ensure the sustainability of the digital ecosystem within the school environment.